Umiędzynarodowienie problemu demograficznego - Horváth, Robert A. (Wydział Prawa i Administracji UAM, 1981)
The author revives the brilliant past of demographic science, with after its final start in the 17-th and 18-th centuries found its proper denomination in the middle of the 19-th century after some hesitation and its definite shape among other disciplines only on the turn of the 19-th and 20-th centuries. From this time on its importance and significance was rapidly growing, especially in international life among social sciences and international practice. The author raises the question of how the process of the internationalization of the demographic problem was produced in the 20-th century, by evocating the main stages of this process, At the beginning in 1927, it was the League of Nations that took the initiative to create an International Union for the Scientific Study of Population. It was inaugurated in 1928 and held its first world congress in London in 1931. In this international scientific framework, however, only the demographic problems of the great powers were dealt with, i.e. the failure of the rigidly formulated Malthusian tenets and their possible consequences for the Western world. In this scientific climate the problems of the losers of World War 1 passed unnoticed, despite the fact that radical views of the internationalization of the demographic problem were elaborated and even politically exploited under the „Lebensraum" — theories aspect. This antagonism soon became apparent by the disruption of the 1937 Berlin Congress of the IUSSP, the 1947 reorganization of which started a new era in the internationalization of the demographic problem. This new period was again characterized by the prevailing authority of the new international body, the United Nations organizations, and by a shift of the international demographic problem towards the developing nations and their „demographic explosion". The international demographic congresses held after 1947 were desperately struggling with the complexity of the problem involving demography, population policy, economics and even sociology. Despite efforts to accumulate a solid scientific basis to the solution of the internationalized, demographic problems, they have not brought up generalized solutions, optimists and pessimists remaining strongly divided. These major difficulties worked in favour of a kind of „nationalization" of the problem around 1965 by looking for different national ways and means of the solution in the developing countries with admission of the necessity of restrictive population policies. From this time on a trend toward the international politicization of the problem is perceptible in demography as a new approximation on the side of or superposed on the mainly demographic or economic policy alternatives. The result of this change in scientific approximation may be seen in the 1974 Bucharest Congress held under the auspices of the UNO and the underlying World Population Plan of Action and its linkage with human rights and women liberation. The author claims that the provisions of this plan for international co-operation are opening up a new era in this field, the development of which may not yet be foreseen in its main aspects, but may be characterized by its optimistic approach to the problem.
The Internationalization of the Demographic Problem